Study of the inhibition effect of two polymers on calcium carbonate formation by fast controlled precipitation method and quartz crystal microbalance. (September 2015) - Peronno, Dimitri; Cheap-Charpentier, Hélène; Horner, Olivier; Perrot, Hubert
Abstract: In this paper, the inhibition efficiency of two inhibitors, namely poly(acrylic acid- co -maleic acid) and polyaspartic acid, towards calcium carbonate scaling was evaluated using fast controlled precipitation (FCP) method and electrochemical quartz crystal microbalance (EQCM). FCP method gave some insight to the calcium carbonate precipitation in solution, whereas EQCM was used to study the calcium carbonate formation on a metallic substrate. It has been shown that these polymers were efficient to delay or to prevent nucleation/growth process, depending on their concentration. Moreover they significantly decreased the crystal growth rate. The FCP method showed that these inhibitors were very efficient at low concentrations (4 mg L −1 ) when no precipitation occurred. In addition, EQCM showed that the surface coverage of deposits on a substrate was reduced by the presence of these inhibitors at very low concentration (4 mg L −1 ). Scanning electronic microscopy and X-ray diffraction showed that the presence of these polymers modified the morphology of calcium carbonate crystal. In order to model nucleation/growth process of calcium carbonate on surface, mass–time transients were interpreted using a 3D model based on a nucleation following a Poisson law associated to vertical and lateral growth rates.